The Analysis Of The Influence Of Investment Knowledge, Minimum Investment Capital, And Investment Risk On Student Interest In Stock Investment In The Indonesian Capital Market (Case Study of Semarang City Students) - Putri Aditya, Puspa (International Journal of Management and Business Economics, 2025)
This study aims to analyze the effect of investment knowledge, minimum investment capital, and investment risk on student interest in stock investment in the Indonesian capital market, with a case study of students in Semarang City. This research uses a quantitative approach with data collection through questionnaires distributed to 100 respondents consisting of students in Semarang City using purposive sampling technique. The research instrument was tested using validity and reliability tests, while the data analysis technique used the classical assumption test, multiple regression analysis, F test, and t test (partial). The results of this study show partially that investment knowledge has no significant effect on investment interest, while investment capital and investment risk have a significant influence on student investment interest in the capital market. These findings provide valuable insights for educational institutions, the government, and the capital market industry in designing educational programs that can increase interest in stock investment among the younger generation.